Artisans in Diyarbakir between XVITh and XIXTh Century During the Ottoman Period - Yılmazçelik, İbrahim (Celal ÖNEY, 2021)
[EN] The origins of trades in the Ottoman society extend back to the earlier Turkish-Islamic states. This widespread organization seen in Ottoman city life. It is accepted as a continuation of the ahiye movement in the XIIIth-XIVth centuries. However, From the beginning of the XVIth century, with the weakening of the Ottoman central authority, it lost its original character. Tradition organization, which is an example of a similar organization of community groups with common ideals and interests in Ottoman society, was a widespread system that organized the whole urban population except the military branches. This organization, as well as being important in the management and economy of the city, provided the basis for the social life of arts and traders, as well as of transportation and service workers. In this study, the artisan organization which has a great prescription in the Ottoman cities will be dealt with in the example of Diyarbakır city. The historical process of the cities reveals the characteristics of that city. These include cities; Historical Cities and Newly Established Cities. From this point of view Diyarbakir (Diyarbekr) is a historical city and it is of great importance that the artisan organization, especially the Ottoman period historical development. Diyarbakir, at Southeast and Eastern Anatolia has been a major commercial center throughout history. The caravan route from Anatolia to the Mesopotamian region passed through this region. During the Ottoman period, the roads coming and going from Iran, Iraq and Azerbaijan intersected in Diyarbakir. Between XVI.th and XVIII.th centuries, Diyarbakir was an important center especially on Van, Aleppo and Baghdad roads. Because the caravans coming from the country gave customs tax in Diyarbakir. In this respect, there are many commercial centers in the city, especially the number of inns and bazaars. For this reason, it has a very lively commercial life, and the number of tradespeople operating in the city was also considerably high. In this study, Between XVIth-XIXth centuries Diyarbakir tradesmen will be dealt with in all aspects, organization in the city and relations with the public will be revealed. In addition, the situation in terms of trade and production and its contribution to the city economy will be examined in detail based on archive resources.

Osmanlı toplumundaki esnaflığın kökenleri daha önceki Türk-İslâm devletlerine kadar uzanmaktadır. Osmanlı şehir hayatında görülen bu yaygın teşkilât, XIII-XIV. yüzyıllardaki ahî hareketinin bir devamı olarak kabul edilmektedir. Ancak, XVI. yüzyıldan itibaren Osmanlı merkezi otoritesinin zayıflamasıyla, ilk zamanlardaki karakterini kaybetmiştir. Osmanlı toplumundaki ortak ideal ve çıkarları olan toplum gruplarının benzer biçimde teşkilatlanmasının bir örneği olan esnaf teşkilâtı, askerî zümreler haricindeki bütün şehirli nüfusu bünyesinde örgütlenmiş olarak bulunduran yaygın bir sistemdi. Bu teşkilât, şehrin yönetimi ve ekonomisinde sahip olduğu önem yanında, sanat ve ticaretle uğraşanlarla, ulaşım ve hizmet işçilerinin de sosyal hayatlarında temeloluşturmaktaydı. Bu çalışmada, Osmanlı şehirlerinde büyük bir öneme sahip olan esnaf teşkilatı Diyarbakır şehri örneğinde ele alınacaktır. Şehirlerin geçirdiği tarihî süreç, o şehrin karakteristik özelliklerini de ortaya koymaktadır. Bu bakımdan şehirleri; Tarihî Şehirler ve Yeni Kurulan Şehirler, olmak üzere ikiye ayırmak mümkündür. Bu açıdan bakıldığında Diyarbakır (Diyarbekr) tarihi bir şehir olup, esnaf teşkilatının özellikle de Osmanlı dönemindeki tarihi gelişiminin ortaya konulması büyük bir önem taşımaktadır. Diyarbakır, Güneydoğu ve Doğu Anadolu’nun önemli bir ticaret merkezi olma özelliğini tarihi boyunca sürdürmüştür. Anadolu’dan Mezopotamya bölgesine giden kervan yoları bu bölgeden geçmekteydi. Osmanlı devleti zamanında da İran, Irak ve Azerbaycan'dan gelen ve giden yollar, Diyarbakır'da kesişmekteydi. XVI ve XVIII. yüzyıllar arasında, Diyarbakır özellikle Van, Halep ve Bağdat yolları üzerinde önemli bir merkezdi. Zira Doğudan gelen kervanlar, Diyarbakır'da gümrük vergisi vermekteydi. Bu bakımdan şehirde pek çok ticaret merkezi bulunmakta olup, özellikle han ve çarşıların sayısı bir hayli fazlaydı. Bu sebeple oldukça canlı bir ticari hayata sahip olup, şehirde faaliyet gösteren esnaf guruplarının sayılarının da oldukça fazlaydı. Bu çalışmada XVI-XIX. yüzyıllar arasında Diyarbakır esnafı bütün yönleri ile ele alınacak, şehirdeki teşkilatlanması ve halk ile olan münasebetleri ortaya konulacaktır. Ayrıca ticaret ve üretim açısından durumları ve şehir ekonomisine katkıları arşiv kaynaklarına dayalı olarak ayrıntılı olarak incelenecektir.
Osmanlı Döneminde XVI. ve XIX. Yüzyıllar Arasında Diyarbakır Esnafı